Co-Constructing Organizational Identity and Culture With Those We Serve: An Ethnography of a Transgender Nonprofit Organization Communicating Family Identity and Identification. (April 2021) - Eger, Elizabeth K.
In this article, I theorize how communication creates participants' organizational identification with nonprofit organizations (NPOs) and their co-construction of organizational identities. Findings from my 3-year organizational ethnography of an NPO serving transgender people, the Transgender Resource Center of New Mexico (TGRC), showcase how Directors, staff, and "guests" (those being served by the NPO) co-constructed a "family" organizational identity and their subsequent organizational identification through communication. My analysis reveals how TGRC's shared cultural values, physical space, language, and artifacts both supported and shaped their family organizational identity. Ethnographic findings illustrate how TGRC participants constructed family through cultural elements including TGRC as a home space while simultaneously going beyond an organizational container to embrace discourses and texts to construct their identity. I end with calls for future research on organizational culture, identity, and identification co-construction to include the people organizations serve and for more ethnographic and arts-based research to enrich such pursuits.